Quantum dot polyurethane emulsion water-based paint

Cobalt selenide iron-nickel quantum dots were synthesized by hydrothermal method and used for the preparation of polyurethane emulsions, which solved the problem of limited quantum dot varieties and realized the aqueous polyurethane emulsion with high crosslinking network, fluorescence performance and ultraviolet absorption functions, suitable for buildings Indicates the coating field.

CN119432218APending Publication Date: 2025-02-14范斌
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411632836.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, there are limited quantum dot varieties, especially the research on nickel-containing fluorescent quantum dots, which limits the expansion and improvement of quantum dot theory and practical applications.

Method used

Carboxy modified cobalt selenide iron-nickel quantum dots with carboxyl groups of 5-15 nm were synthesized by hydrothermal method and used to prepare polyurethane emulsions to form aqueous polyurethane emulsions with high crosslinking network, fluorescence properties and ultraviolet absorption functions. .

Benefits of technology

Aqueous polyurethane emulsions with good transparency, photoluminescence and ultraviolet absorption properties are achieved, suitable for the field of architectural indicator coatings, and the application range of quantum dots is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

According to the quantum dot polyurethane emulsion water-based paint provided by the invention, the water-based polyurethane emulsion with a high cross-linked network, fluorescence performance and an ultraviolet absorption function is prepared from the polyurethane emulsion, particularly, the water-based polyurethane emulsion has good transparency, photoluminescence and ultraviolet absorption performance, and can be applied to the field of building indication paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of architectural coatings, and relates to a quantum dot polyurethane emulsion water-based coating, and in particular to a preparation method and application of selenide quantum dots and polyurethane emulsion. Background Art

[0002] Polyurethane (PU) is a multifunctional material with excellent properties such as good bending resilience, high strength and good density. It is considered to be one of the most widely used synthetic materials in the world. Since most organic solvents in solvent-based polymers are volatile and easy to pollute the environment, the use of organic solvents is restricted worldwide, so environmentally friendly products are highly valued in the industry. Technologies with low VOCs emissions have also gained a larger industrial share. Because water is a green, pollution-free, environmentally friendly solvent, it is an irreplaceable choice in the synthesis and manufacture of chemical products, and can also improve the speed and efficiency of various organic reactions. Waterborne polyurethane is a new type of environmentally friendly polymer material. Waterborne polyurethane chains can be effectively dispersed in water, and have good stability and excellent film-forming properties; at the same time, it also has the characteristics of not easy to burn, low odor, environmentally friendly, convenient processing and modification, good biocompatibility, energy and resource saving, etc., which meet the requirements of economic development, and can also retain the many excellent properties of traditional solvent-based polyurethanes such as wear resistance, flexibility, low temperature resistance and fatigue resistance. Therefore, waterborne polyurethane gradually replaces solvent-based polyurethane and becomes a green and environmentally friendly "new material".

[0003] The emulsification method of waterborne polyurethane is generally divided into external emulsification method and internal emulsification method. First, prepare PU with a certain relative molecular mass, and then use water as a solvent and disperse it in water under the action of an emulsifier by high-speed stirring to obtain a stable WPU dispersed emulsion. At present, waterborne polyurethane emulsion is mainly based on the internal emulsification method, which is also called the self-emulsification method. It refers to adding hydrophilic ions or hydrophilic groups to the WPU molecular chain, giving the waterborne polyurethane a certain hydrophilic property. It is a method that can be emulsified without adding an emulsifier. The self-emulsification method mainly includes acetone method, prepolymer dispersion method, melt dispersion method and ketimine-ketazine method. The most commonly used methods in the preparation of polyurethane are acetone modification method and prepolymer dispersion method.

[0004] Waterborne polyurethane is an environmentally friendly material, so it is more widely used and studied, and has received more and more attention. Therefore, it is of great significance to develop waterborne polyurethane with multiple functions. For example, waterborne polyurethane is prepared into waterproof coatings and continuously improved to have good mechanical properties and waterproof properties. There are also small molecules with various functional dihydroxyl and amino groups that are commonly used as chain extenders to synthesize waterborne polyurethane. At present, the chromophores of waterborne polyurethane fluorescent materials mainly include azo, anthraquinone, pyran and other types of fluorescent substances.

[0005] Quantum dots, also known as semiconductor nanocrystals, are zero-dimensional nanocrystalline materials composed of compounds of II-VI or III-V group elements, with a particle size between 1-20nm. The name of quantum dots comes from the material's significant quantum confinement effect, that is, the material's own particle size is close to or smaller than the Bohr radius. At this time, the movement of carriers (electrons and holes) inside the semiconductor is restricted in all directions, causing the material's original continuous electronic structure to be quantized and confined, resulting in a discontinuous discrete energy band structure like an atom, so quantum dots are also called "artificial atoms."

[0006] For example, Xiamen University CN105131806A water-based fluorescent polyurethane coating and its prepolymer mixing method preparation method, which involves fluorescent materials and preparation methods thereof. The water-based fluorescent polyurethane coating is composed of a polyurethane resin phase and an inorganic fluorescent quantum dot phase. The prepolymer mixing method is adopted, the polyurethane prepolymer is used as the mother liquid, the CdSe prepolymer is injected, and it is directly heated to complete the preparation of polyurethane and CdSe respectively; finally, a water-based fluorescent polyurethane coating that emits yellow-white light after ultraviolet excitation is obtained. It avoids the phase separation problem existing in the existing physical mixing method, and can also be carried out at a lower temperature, the reaction is mild, the operation is simple, and the emission band of the obtained fluorescent coating can change from green light to yellow light under ultraviolet excitation; finally, a series of fluorescent coatings with short curing time, excellent hydrophobic properties, high hardness, and good fluorescence effect are obtained. It still has a strong photoluminescence effect in the water phase film. The invention consists of a polyurethane resin phase and an inorganic fluorescent quantum dot phase. The composition and mass percentage of the raw materials for preparing the system are as follows: the polyurethane phase includes 20% to 25% of diisocyanate, 50% to 55% of diol, 0.05% to 0.08% of an organic tin catalyst, 5% to 8% of a hydrophilic chain extender, 4% to 5% of a capping agent, 5% to 7% of a neutralizing agent, and 0.3% to 0.5% of a free radical catalyst; the inorganic fluorescent CdSe quantum dot phase includes 0.007% to 0.009% of selenium powder, 0.004% to 0.006% of sodium borohydride, 0.02% to 0.03% of chromium chloride, and 0.02% to 0.04% of mercaptopropionic acid; the remainder is water; and the volume ratio of the quantum dot prepolymer of the inorganic fluorescent quantum dot phase to the prepolymer of the polyurethane resin phase is (1 to 2):1.

[0007] For example, CN107266988A of Soochow University provides a colorful graphene quantum dot coating and its preparation method and application, which relates to the field of coating technology. It is mainly prepared from the following raw materials by mass: 5-40 parts of graphene quantum dots, 3-10 parts of pigments, 90-120 parts of matrix resin, 330-370 parts of deionized water, 450-550 parts of fillers, and the sum of all raw materials is 1000 parts; it alleviates the technical problems of existing coatings such as single color tone, lack of colorfulness, and easy visual aesthetic fatigue, and achieves the technical effect of not only having good antibacterial properties, but also being able to show colorful colors with a wider chromatographic range, thereby effectively alleviating people's visual aesthetic fatigue and meeting people's demand for diversified coating colors.

[0008] For example, Nanjing University of Technology has developed a nickel-containing fluorescent quantum dot, which has low toxicity, a wide absorption spectrum and a narrow fluorescence emission spectrum, and the luminescent color is adjustable with the excitation wavelength, with high luminous efficiency and good stability, and can be used to construct quantum dot solar sensitized cells and LED devices. The nickel-containing fluorescent quantum dots of the present invention include one or a combination of nickel selenide, nickel telluride, and nickel sulfide, with a quantum dot particle size of 2 to 20 nm, a quantum yield of 10 to 60%, and a half-peak width of the photoluminescence spectrum of 30 to 130 nm; preferably, the fluorescent quantum dots of NiSe when x=0.5, such quantum dots have low toxicity, a wide absorption spectrum and a narrow fluorescence emission spectrum, and the luminescent color is adjustable with the excitation wavelength, with high luminous efficiency and good stability, and can be used to construct quantum dot solar sensitized cells and LED devices.

[0009] Although the research on quantum dots has been developed for decades, the varieties of quantum dots are still relatively limited. At present, the most in-depth research on the theory and application of quantum dots is only II-VI and III-V semiconductor nanocrystals, such as CdS, ZnS, CdTe, CdSe, InP, etc., which greatly limits the expansion and improvement of quantum dot theory and practical applications. Therefore, the development of a new type of quantum dot material will be of far-reaching significance. At present, most of the research on nickel-containing semiconductor materials remains at the level of macroscopic bulk materials. Only a few studies involve the nanoscale of the material, and there is no report on nickel-containing fluorescent quantum dots. Therefore, it is of great significance to find a simple and feasible preparation method, develop a new type of nickel-containing fluorescent quantum dot, expand new members for the quantum dot family, and expand the application range of quantum dots. Summary of the invention

[0010] The invention provides a quantum dot polyurethane emulsion water-based paint, in particular, a carboxyl-modified cobalt iron nickel selenide quantum dot particle with a size of 5-15nm is prepared, and the particle is used in the preparation of polyurethane emulsion to obtain a water-based polyurethane emulsion with a highly cross-linked network, fluorescence performance and ultraviolet absorption function, especially good transparency, photoluminescence and ultraviolet absorption performance, and can be used in the field of architectural indication coatings.

[0011] Specifically: A multifunctional quantum dot water-based architectural paint, wherein the quantum dot material is cobalt iron nickel selenide with a size of 5-15 nm, and the cobalt iron nickel selenide is prepared by the following steps: (1) Dissolve appropriate amounts of nickel acetate tetrahydrate, ferrous chloride tetrahydrate, and cobalt nitrate hexahydrate in N,N-dimethylformamide, ethanol, glycerol, and deionized water, stir, and mix well to obtain solution A; (2) Mix selenium powder and hydrazine hydrate, seal, heat to 52°C, keep constant temperature for 1 hour under stirring, and cool naturally to obtain solution B; (3) Liquid A was introduced into liquid B, and then introduced into a hydrothermal reactor, the temperature was raised to 130°C at a rate of 1°C / min, the temperature was kept constant for 48 hours, and then naturally cooled; (4) The hydrothermal reaction product and its solution were extracted and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-1 liquid; the lower centrifuge product was taken and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-2 liquid; (5) Repeat step (4) until liquid C-5 is obtained; (6) After C-1, C-2, C-3, C-4 and C-5 are evenly mixed, centrifuge them and take the centrifuge product from the centrifuge tube; (7) The centrifuged product was introduced into a mixed solution of oleic acid and tetrahydrofuran, and after ultrasonic vibration for 3 hours, it was diluted 3 times with 2:1 ethanol and deionized water, stirred evenly, and centrifuged at a speed of 13000 r / min for 5 min. The solid product at the bottom of the centrifuge tube was collected and dried in a vacuum oven at 35°C to obtain cobalt iron nickel selenide quantum dots.

[0012] Furthermore, the coating is polyester, alkyd resin, acrylic acid, polyurethane, epoxy resin, vinyl resin, polyamide, siloxane, or a mixture of these polymers.

[0013] Furthermore, in step (1), 0.34 mmol nickel acetate tetrahydrate, 0.08 mmol ferrous chloride tetrahydrate, and 0.06 mmol cobalt nitrate hexahydrate are dissolved in 40 mL N,N-dimethylformamide, 2 mL ethanol, 4 mL glycerol, and 3 mL deionized water.

[0014] Further, 0.6 mmol of selenium powder was mixed with 2 ml of hydrazine hydrate.

[0015] Furthermore, in step (3), a hydrothermal reactor is vented with nitrogen.

[0016] Furthermore, in step (6), centrifugation was performed in a centrifuge at 12000 rpm for 5 min.

[0017] Furthermore, 50 mg of the centrifuged product in step (7) was introduced into 10 g of a 5 wt % oleic acid-tetrahydrofuran mixed solution.

[0018] A quantum dot polyurethane emulsion water-based coating is prepared by the following steps: (a) 30-40 parts by weight of macromolecular polyol polyethylene adipate is added to a reaction bottle, and the mixture is distilled under reduced pressure at 100-105° C. for 15-20 minutes, then cooled to 60-70° C., 30-50 parts of hexamethylene diisocyanate and 0.3-0.5 parts of stannous octoate catalyst are added, and the mixture is heated to 80-90° C. for reaction for 1.5-2 hours; (b) cooling to 50-60° C., adding 4-5 parts of diethylene glycol small molecule alcohol chain extender and 5.0-5.4 parts of 2,2-dimethylol propionic acid small molecule hydrophilic chain extender, adding 10-20 parts of 1 mL aqueous solution containing 250 μg of quantum dots, and heating to 75-85° C. for reaction for 2-3 hours; (c) Cooling to 40-45°C, using acetone to reduce the viscosity, reacting for 20 minutes, adjusting the pH to about 7.5 using trimethylamine, adding 0°C deionized water under high-speed stirring to obtain a quantum dot polyurethane emulsion.

[0019] A quantum dot polyurethane emulsion water-based coating is prepared by the following steps: (a) 35 parts by weight of macromolecular polyol polyethylene adipate was added to a reaction bottle, and the mixture was distilled under reduced pressure at 100° C. for 20 minutes, then cooled to 60° C., 40 parts of hexamethylene diisocyanate and 0.4 parts of stannous octoate catalyst were added, and the mixture was heated to 90° C. for reaction for 2 hours; (b) cooling to 60°C, adding 4.5 parts of diethylene glycol small molecule alcohol chain extender and 5.2 parts of 2,2-dihydroxymethyl propionic acid small molecule hydrophilic chain extender, adding 10 parts of 1 mL aqueous solution containing 250 μg of quantum dots, and heating to 80°C for reaction for 3 hours; (c) The temperature was lowered to 40°C, acetone was used to reduce the viscosity, and after reacting for 20 minutes, trimethylamine was used to adjust the pH to 7.5, and 0°C deionized water was added under high-speed stirring to obtain a quantum dot polyurethane emulsion.

[0020] The present invention first uses a hydrothermal method to synthesize quantum dots, see attached Figure 1 and attached Figure 2 It can be seen that the size of the obtained quantum dots is concentrated in the range of 5-15 nm. XPS test and peak fitting can clearly infer that the selenide quantum dots prepared hydrothermally in the present invention are in a selenide alloy state without any oxides, that is, the corresponding fluorescence effect is excellent.

[0021] The prepared hydrothermal product is then subjected to multiple centrifugation to separate the upper and lower liquids. This step directly affects the size of the product. If the size is too large, there will be no fluorescence or corresponding quantum effect. This step is indispensable or can be replaced at will.

[0022] The centrifugal separation product is then carboxylated to improve the water solubility of the quantum dots in the subsequent polyurethane emulsion preparation process, and even participate in the specific process of polyurethane, thereby obtaining a uniformly dispersed polyurethane quantum dot solution. For details, see the attached Figure 3 .

[0023] See attached Figure 3 The fluorescence of Example 2 is significantly stronger than that of Comparative Example 1, while the pure polyurethane emulsion is non-fluorescent. In addition, the maximum emission wavelength of Example 2 (458 nm) is blue-shifted by 24 nm compared with that of Comparative Example 2 (482 nm). The specific effects can be seen in the attached Figure 3 In addition, the fluorescence spectrum position is in the blue fluorescence area in the CIE coordinate.

[0024] Beneficial technical effects: (1) The size of quantum dots prepared by the hydrothermal centrifugation method is relatively uniform, the yield of quantum dots is high, the method is simple and cost-effective; (2) The hydrothermal centrifugation product is a selenized multi-metal alloy in a non-oxidized state; (3) After the surface of the quantum dots is functionalized with carboxyl groups, the dispersibility in the polyurethane emulsion raw material is greatly improved, and a strong interface effect of covalent bond transition can be formed with the raw material; (4) The polyurethane emulsion is prepared to obtain an aqueous polyurethane emulsion with a highly cross-linked network, fluorescent properties and ultraviolet absorption functions, especially with good transparency, photoluminescence and ultraviolet absorption properties, and can be used in the field of architectural indicator coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Attached Figure 1 The morphology of carboxylation-treated quantum dots prepared in Example 1 of the present invention.

[0026] Attached Figure 2 The quantum dot morphology of Example 1 of the present invention after being processed in step (6).

[0027] Attached Figure 3 Fluorescence spectra of polyurethane coatings prepared in Example 1 of the present invention and Comparative Example 2. DETAILED DESCRIPTION Example 1

[0028] A multifunctional quantum dot water-based architectural paint, wherein the quantum dot material is cobalt iron nickel selenide with a size of 5-15 nm, and the cobalt iron nickel selenide is prepared by the following steps: (1) Dissolve appropriate amounts of 0.34 mmol nickel acetate tetrahydrate, 0.08 mmol ferrous chloride tetrahydrate, and 0.06 mmol cobalt nitrate hexahydrate in 40 mL N,N-dimethylformamide, 2 mL ethanol, 4 mL propylene glycol, and 3 mL deionized water, stir, and mix well to obtain solution A; (2) Mix 0.6 mmol of selenium powder with 2 ml of hydrazine hydrate, seal, heat to 52 °C, keep constant temperature for 1 h with stirring, and cool naturally to obtain solution B; (3) Liquid A was introduced into liquid B, and then introduced into a hydrothermal reactor evacuated with nitrogen, and the temperature was raised to 130°C at a rate of 1°C / min, kept at a constant temperature for 48 hours, and cooled naturally; (4) The hydrothermal reaction product and its solution were extracted and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-1 liquid; the lower centrifuge product was taken and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-2 liquid; (5) Repeat step (4) until liquid C-5 is obtained; (6) After C-1, C-2, C-3, C-4, and C-5 are evenly mixed, centrifuge at 12,000 rpm for 5 min, and the bottom centrifuge product is taken from the centrifuge tube; (7) 50 mg of the centrifuged product was introduced into 10 g of a 5 wt% oleic acid-tetrahydrofuran mixed solution, and after ultrasonic vibration for 3 hours, it was diluted 3 times with 2:1 ethanol-deionized water, stirred evenly, and centrifuged at 13000 r / min for 5 min. The solid product at the bottom of the centrifuge tube was collected and dried in a vacuum oven at 35°C to obtain cobalt iron nickel selenide quantum dots.

[0029] The cobalt iron nickel selenide quantum dots are used for the preparation of polyurethane emulsion: (a) 35 parts by weight of macromolecular polyol polyethylene adipate was added to a reaction bottle, and the mixture was distilled under reduced pressure at 100° C. for 20 minutes, then cooled to 60° C., 40 parts of hexamethylene diisocyanate and 0.4 parts of stannous octoate catalyst were added, and the mixture was heated to 90° C. for reaction for 2 hours; (b) cooling to 60°C, adding 4.5 parts of diethylene glycol small molecule alcohol chain extender and 5.2 parts of 2,2-dihydroxymethyl propionic acid small molecule hydrophilic chain extender, adding 10 parts of 1 mL aqueous solution containing 250 μg of quantum dots, and heating to 80°C for reaction for 3 hours; (c) Cooling to 40°C, using acetone to reduce the viscosity, reacting for 15-30 minutes, adjusting the pH to 7.5 using trimethylamine, adding 0°C deionized water under high-speed stirring to obtain a quantum dot polyurethane emulsion.

[0030] Comparative Example 1 A multifunctional quantum dot water-based architectural coating, wherein the quantum dot material is cobalt nickel selenide, is prepared by the following steps: (1) Dissolve an appropriate amount of 0.34 mmol nickel acetate tetrahydrate and 0.08 mmol ferrous chloride tetrahydrate in 40 mL N,N-dimethylformamide, 2 mL ethanol, 4 mL propylene glycol and 3 mL deionized water, stir and mix well to obtain solution A; (2) Mix 0.6 mmol of selenium powder with 2 ml of hydrazine hydrate, seal, heat to 52 °C, keep constant temperature for 1 h with stirring, and cool naturally to obtain solution B; (3) Liquid A was introduced into liquid B, and then introduced into a hydrothermal reactor evacuated with nitrogen, and the temperature was raised to 130°C at a rate of 1°C / min, and the temperature was kept constant for 48 hours, and then naturally cooled; (4) The hydrothermal reaction product and its solution were extracted and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-1 liquid; the lower centrifuge product was taken and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-2 liquid; (5) Repeat step (4) until liquid C-5 is obtained; (6) After C-1, C-2, C-3, C-4, and C-5 are evenly mixed, centrifuge for 5 minutes using a 12,000 rpm centrifuge, and the centrifuge product at the bottom of the centrifuge tube is taken; after drying in a vacuum oven at 35°C, cobalt iron nickel quantum dots are obtained.

[0031] The quantum dots are used for the preparation of polyurethane emulsion: (a) 35 parts by weight of macromolecular polyol polyethylene adipate was added to a reaction bottle, and the mixture was distilled under reduced pressure at 100° C. for 20 minutes, then cooled to 60° C., 40 parts of hexamethylene diisocyanate and 0.4 parts of stannous octoate catalyst were added, and the mixture was heated to 90° C. for reaction for 2 hours; (b) cooling to 60°C, adding 4.5 parts of diethylene glycol small molecule alcohol chain extender and 5.2 parts of 2,2-dihydroxymethyl propionic acid small molecule hydrophilic chain extender, adding 10 parts of 1 mL aqueous solution containing 250 μg of quantum dots, and heating to 80°C for reaction for 3 hours; (c) Cooling to 40°C, using acetone to reduce the viscosity, reacting for 15-30 minutes, adjusting the pH to 7.5 using trimethylamine, adding 0°C deionized water under high-speed stirring to obtain a quantum dot polyurethane emulsion. Example 2

[0032] A multifunctional quantum dot water-based architectural paint, wherein the quantum dot material is cobalt iron nickel selenide with a size of 5-15 nm, and the cobalt iron nickel selenide is prepared by the following steps: (1) Dissolve appropriate amounts of 0.34 mmol nickel acetate tetrahydrate, 0.08 mmol ferrous chloride tetrahydrate, and 0.06 mmol cobalt nitrate hexahydrate in 40 mL N,N-dimethylformamide, 2 mL ethanol, 4 mL propylene glycol, and 3 mL deionized water, stir, and mix well to obtain solution A; (2) Mix 0.6 mmol of selenium powder with 2 ml of hydrazine hydrate, seal, heat to 52 °C, keep constant temperature for 1 h with stirring, and cool naturally to obtain solution B; (3) Liquid A was introduced into liquid B, and then introduced into a hydrothermal reactor evacuated with nitrogen, and the temperature was raised to 130°C at a rate of 1°C / min, kept at a constant temperature for 48 hours, and cooled naturally; (4) The hydrothermal reaction product and its solution were extracted and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-1 liquid; the lower centrifuge product was taken and diluted 3 times with 2:1 ethanol deionized water, stirred evenly, and centrifuged at 2000 rpm for 2 min. The upper liquid in the centrifuge tube was taken as C-2 liquid; (5) Repeat step (4) until liquid C-5 is obtained; (6) After C-1, C-2, C-3, C-4, and C-5 are evenly mixed, centrifuge at 12,000 rpm for 5 min, and the bottom centrifuge product is taken from the centrifuge tube; (7) 50 mg of the centrifuged product was introduced into 10 g of a 5 wt% oleic acid-tetrahydrofuran mixed solution, and after ultrasonic vibration for 3 hours, it was diluted 3 times with 2:1 ethanol-deionized water, stirred evenly, and centrifuged at 13000 r / min for 5 min. The solid product at the bottom of the centrifuge tube was collected and dried in a vacuum oven at 35°C to obtain cobalt iron nickel selenide quantum dots.

[0033] In addition, the UV transmission spectrum of the polyurethane coating of Example 1 and the blank was tested. The UV shielding spectrum of the blank polyurethane was The UV shielding range of the quantum dot polyurethane in Example 1 is between 300-325 nm, while the UV shielding range of 300-400 nm is significantly increased, that is, the quantum dot polyurethane of the present invention can also be applied to the field of UV protection buildings.

[0034] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A quantum dot polyurethane emulsion water-based coating, characterized in that Prepared by the following steps: (a) adding 30-40 parts by weight of macromolecular polyol polyethylene adipate to a reaction bottle, distilling under reduced pressure at 100-105° C. for 15-20 minutes, cooling to 60-70° C., adding 30-50 parts by weight of hexamethylene diisocyanate and 0.3-0.5 parts of stannous octoate catalyst, heating to 80-90° C. and reacting for 1.5-2 hours; (b) cooling to 50-60° C., adding 4-5 parts by weight of diethylene glycol small molecule alcohol chain extender and 5.0-5.4 parts by weight of 2,2-dimethylol propionic acid small molecule hydrophilic chain extender, adding 10-20 parts by weight of 1 mL of an aqueous solution containing 250 μg of quantum dots, and heating to 75-85° C. for reaction for 2-3 hours; (c) Cooling to 40-45°C, using acetone to reduce the viscosity, reacting for 15-30 minutes, adjusting the pH to about 7.5 using trimethylamine, adding 0°C deionized water under high-speed stirring to obtain a quantum dot polyurethane emulsion.

2. A quantum dot polyurethane emulsion water-based coating, characterized in that Prepared by the following steps: (a) 35 parts by weight of macromolecular polyol polyethylene adipate was added to a reaction bottle, and the mixture was distilled under reduced pressure at 100° C. for 20 minutes, then cooled to 60° C., 40 parts by weight of hexamethylene diisocyanate and 0.4 parts by weight of stannous octoate catalyst were added, and the mixture was heated to 90° C. for reaction for 2 hours; (b) cooling to 60° C., adding 4.5 parts by weight of diethylene glycol small molecule alcohol chain extender and 5.2 parts by weight of 2,2-dimethylol propionic acid small molecule hydrophilic chain extender, adding 10 parts by weight of 1 mL of an aqueous solution containing 250 μg of quantum dots, and heating to 80° C. for reaction for 3 hours; (c) Cooling to 40°C, using acetone to reduce the viscosity, reacting for 15-30 minutes, adjusting the pH to 7.5 using trimethylamine, adding 0°C deionized water under high-speed stirring to obtain a quantum dot polyurethane emulsion.

3. A quantum dot polyurethane emulsion water-based paint as claimed in claim 1 or 2, characterized in that The material of quantum dots is cobalt iron nickel selenide, and the size is 5-15nm.

Citation Information

Patent Citations

  • Colorful graphene quantum dot coating and preparation method and application thereof

    CN107266988A

  • Nickeliferous fluorescent quantum dot and preparation method and application thereof

    CN102690657A

  • Preparation method of waterborne polyurethane containing fluorescent dye

    CN103275334A

  • Waterborne fluorescent polyurethane coating and preparation method thereof through prepolymer mixing

    CN105131806A

  • Nanometer cobalt diselenide-supported carbon nanofiber composite material, and preparation method and application thereof

    CN109012704A